Strategi Pengembangan Wisata Bahari Di Kawasan Ekosistem Terumbu Karang Negeri Morella - Tuhumena, Lolita; Tomasila, Leopold A.; Salhuteru, Stefani T; Rumahorbo, Basa T (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Morela coastal waters are a tourist area on Ambon Island with the potential to be a coral reef ecosystem. The Increasing number of visitors and lack of understanding of local people and tourists about the importance of developing conservation and marine tourism. Such conditions underlie the importance of research to formulate strategies for the development of coral reef ecosystem tourism. The research was analyzed in situ at two station with analyzed coral cover and SWOT. Based on the results of the study, shows that all the potential of coral reef waters in the coral reef ecosystem tourism from the brightness of the waters, coral cover, types of coral life forms, abundance of coral fish, bottom material of the waters, current speed, water depth, water temperature and beach width, are important values ​​that must be developed. The development strategies obtained are; Increase cooperation between the management, the community, and the government in the development & promotion of marine tourism; Increase the development of tourism that contributes to environmental and cultural conservation; Increase socialization activities and promotion of marine tourism packages to the wider community and abroad through online media; Increase awareness of the surrounding community on the importance of protecting coral reef environmental resources; Improving MCS (Monitoring, controlling and Surveilance) as well as coordination between stakeholders;